2013
DOI: 10.3109/15622975.2013.862345
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retroviruses and ADHD

Abstract: Since the ADHD aetiology is due to a complex interaction of environmental, biological and genetic factors, HERVs may represent one link among these factors and clinical phenotype of ADHD. A future confirmation of HERV-H overexpression in a larger number of ADHD patients will make possible to identify it as a new parameter for this clinical condition, also contributing to deepen the study on the role of HERVs in the neurodevelopment diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…Subsequent quantification showed that HERV-H and HERV-W were, respectively, more and less abundantly expressed in ADS patients [ 162 ]. Similarly, the HERV-H transcript level in ADHD patients PBMC was significantly higher, while no differences were found in HERV-W expression [ 163 ].…”
Section: Herv-w Expression In Neurological and Neuropsychiatric DImentioning
confidence: 99%
“…Subsequent quantification showed that HERV-H and HERV-W were, respectively, more and less abundantly expressed in ADS patients [ 162 ]. Similarly, the HERV-H transcript level in ADHD patients PBMC was significantly higher, while no differences were found in HERV-W expression [ 163 ].…”
Section: Herv-w Expression In Neurological and Neuropsychiatric DImentioning
confidence: 99%
“…Although most HERVs are inactivated or silenced by mutations or epigenetic modifications, they have served important functions in human evolution and speciation, and can potentially cause or contribute to diseases [ 2 , 3 ]. Mounting evidence has demonstrated that HERVs may be involved in the pathological processes of some neurological and psychiatric disorders, such as multiple sclerosis, schizophrenia, and bipolar disorder [ 4 , 5 ], and cancers such as melanoma, breast, prostate, and leukemia [ 6 , 7 ]. Thus, investigating HERVs is important for understanding the etiological mechanisms of certain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Perron and colleagues found that a higher level of HERV‐W expression in schizophrenia was associated with a lower copy‐number of HERV‐W elements [Perron et al, ]. Similar findings on HERV's transcriptional activity were also reported for other neuropsychiatric disorders such as bipolar disorder [Frank et al, ; Weis et al, ; Perron et al, ], major depression [Weis et al, ], autism [Balestrieri et al, ], and ADHD [Balestrieri et al, ]. While most of these studies focused on the overall detection of qualitative and quantitative profiles of HERVs transcriptional activity, two reports specifically addressed the effect of abnormal transcriptional profiles on gene activity.…”
Section: The Impact Of Tes On the Human Genome And The Central Nervoumentioning
confidence: 78%